Depth and temperature preference of anadromous Arctic char Salvelinus alpinus in the Kitikmeot Sea, a shallow and low-salinity area of the Canadian Arctic - Harris, Les N.; Yurkowski, David J.; Gilbert, Matthew J.H.; Else, Brent G.T.; Duke, Patrick J.; Ahmed, Mohamed M.M.; Tallman, Ross F.; Fisk, Aaron T.; Moore, Jean Sébastien (Marine Ecology Progress Series, 2020)
The Arctic climate is changing rapidly, yet predicting how aquatic species will respond to these changes remains challenging given the lack of empirical data for most high-latitude taxa. Acoustic telemetry has recently emerged as an important methodology for understanding horizontal and vertical space-use patterns in fishes. Here, we used acoustic telemetry to document marine habitat use and depth/temperature preference of 26 anadromous Arctic char Salvelinus alpinus within the Kitikmeot Sea region of the Canadian central Arctic over 4 yr (2013- 2016). Most detections (~70%) were within the top 3 m of the water column, and most were in estuarine (72.6%) vs. marine (27.4%) habitats. Arctic char preferred deeper waters later in the summer, but the temperature they occupied remained relatively constant throughout the marine feeding season (~5-8°C). Most Arctic char exhibited some degree of repetitive diving behavior, with individuals diving to 35 m. Diving activity increased later in the summer marine feeding season and is likely a response to the seasonal transition of their preferred prey to deeper waters as the season progresses. Finally, Arctic char preferred deeper waters with less ice cover and during the day, the latter suggesting potential diel patterns to marine habitat use. Finally, year-to-year variation in Arctic char depth and temperature use was very modest despite differences in climatic and ice conditions. This result suggests that habitat use is relatively fixed and may reflect their thermal and osmoregulatory physiology, which has important implications for forecasting the impacts of a changing Arctic on this economically valuable species.